الجرائم المتعلقة بنزاهة الممارسات التجارية في القانون 02/04. - حنكة, بوبكر (جامعة الوادي University of Eloued, 2019)
تضمن القانون رقم 04-02، أحكام قانونية جديدة، و خاصة توسيع تجريمه للممارسات لم تكن مقنن في القوانين السابق مثل تجريم الممارسات التجارية غير النزيهة و الممارسات التعاقدية التعسفية، وكذا إضافة صور جدیدة للممارسات المجرم سابقا، إضافة إلى قوة حجية المحاضر المحرر من قبل الاعوان المؤهلين و التي لا يطعن فيها إلا بالتزوير. إضافة إلى توسیع مفهوم النشاطات التي یطبق في إطارها قانون الممارسات التجاریة، كما غیر هذا القانون مفهوم حالة العود وعدل بعض العقوبات ووسع من مجال تطبیقها و وفق المشرع فيها وهذا لقمع المخالفة المتعلق بنزاهة الممارسات التجارية. إلا أنه يتطلب المراجع المستمرة عن طريق التحيين أحكامه نظرا للأفعال المستجدة في السوق الوطنية، و لموائمة التشريع الوطني مع الاتفاقيات و الالتزامات الدولية، قصد مواجهة المتغيرات الجديدة، التي يشهدها الاقتصاد العالمي، و ما لذلك من تأثيرات على الاقتصاد الوطني، الذي أصبح من الضروري تكييف التشريع الجزائري معها. Law No. 04-02 guarantees new legal provisions, particularly the criminalization of practices that were not codified in previous laws such as the criminalization of unfair business practices and arbitrary contractual practices, as well as the addition of new images of past criminal practices, as well as the authoritative power of the transcripts Which are only qualified for fraud. In addition to expanding the concept of the activities under which the Commercial Practices Law is applied. This law also changed the concept of the case of oud and amended some penalties and expanded the scope of application and according to legislator in order to suppress the violation of the integrity of commercial practices. However, it requires constant references by updating its provisions in view of the new developments in the national market and the harmonization of national legislation with international conventions and commitments in order to confront the new changes in the global economy and the effects on the national economy. Algerian legislation.
ماستر اعمال